Cytotoxic and antibacterial depsidones from the endophytic fungus Chaetomium brasiliense isolated from Thai rice - Trinop Promgool; Kwanjai Kanokmedhakul; Thianrat Leewijit; Jiaojiao Song; Kasem Soytong; Jantana Yahuafai; Tomas Kudera; Ladislav Kokoška; Somdej Kanokmedhakul (Natural Product Research, 2021)
In addition, a few of them also showed moderate activity against a Gram-negative bacteria
Keywords: Microbial Natural Products and Biosynthesis; Plant Pathogens and Fungal Diseases; Plant-Microbe Interactions and Immunity